Fertility in Holstein cows (Bos taurus) inseminated with sexed semen of Gyr bulls (Bos indicus) in small-scale dairy herds at Irrigation Majes, Arequipa, Peru - Ramos, Olger (2022)
The present study aimed to determine the conception rate at first service and the birth rate, as well as the percentage of female calves born using Gyr sexed semen in Holstein cows. Artificial insemination (AI) was performed on 1174 second and third calving cows during December 2011 to October 2012 in small-scale farms of the Majes Irrigation, Arequipa, Peru. The AI was carried out 12 hours after the visual detection of heat and the pregnancy diagnosis was done by rectal palpation 45-60 days after the service. The conception rate in 2nd calving animals was in a range of 37 to 77%, while for 3rd calving animals it was in the range of 39 to 88%. The birth rate was in the range of 32 to 71% and 38 to 85% for cows of 2nd and 3rd calving, respectively, without evidence of an effect of seasonality on the conception rate or birth rate. The overall conception rate was 56% and the birth rate was 54%. The percentage of female calves was 82% and male calves 18%. It is concluded that the number of births and seasonality do not influence conception and birth rates when using Gyr sexed semen; likewise, the use of Gyr sexed semen in Holstein cows would be a good reproductive option.